2018
DOI: 10.1177/1747493018798535
|View full text |Cite
|
Sign up to set email alerts
|

Frequent, short bouts of light-intensity exercises while standing decreases systolic blood pressure: Breaking Up Sitting Time after Stroke (BUST-Stroke) trial

Abstract: Australian and New Zealand Clinical Trials Registry http://www.anzctr.org.au ANZTR12615001189516.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 29 publications
1
56
0
5
Order By: Relevance
“…17,18 Recent findings have also shown that breaking up prolong sedentary time with short bouts of light PA leads to clinically relevant improvements in systolic blood pressure (3-4 mmHg) in stroke survivors. 41 These findings are encouraging since this approach could be achievable for stroke survivors with limited capacity to ambulate who will find it difficult to reach recommended levels of MVPA. On the other hand, given the potential of engaging in PA among community ambulating stroke survivors, it is quintessential to understand barriers to exercise, specifically related to socio-cultural environments, values, and norms.…”
Section: Discussionmentioning
confidence: 82%
“…17,18 Recent findings have also shown that breaking up prolong sedentary time with short bouts of light PA leads to clinically relevant improvements in systolic blood pressure (3-4 mmHg) in stroke survivors. 41 These findings are encouraging since this approach could be achievable for stroke survivors with limited capacity to ambulate who will find it difficult to reach recommended levels of MVPA. On the other hand, given the potential of engaging in PA among community ambulating stroke survivors, it is quintessential to understand barriers to exercise, specifically related to socio-cultural environments, values, and norms.…”
Section: Discussionmentioning
confidence: 82%
“…The rst target behaviour is to reduce total time spent sedentary (5)(6)(7)(8)(9)(10)(11)(12)14,33). The BUST-study found a statistically and clinically relevant decrease of the systolic blood pressure by interrupting sedentary behaviour every thirty minutes with a walk of three minutes (16). Therefore, the second target behaviour is to reduce time spent in sedentary behaviour accumulated in bouts over thirty minutes.…”
Section: Stage 1: Understanding the Behaviourmentioning
confidence: 99%
“…Additionally, prolonged uninterrupted sedentary time, independent of total sedentary time, is associated with poor health and elevated cardiovascular risk factors (7,(11)(12)(13)(14)(15). In people with stroke a clinical relevant decrease of blood pressure was found by reducing and interrupting sedentary behaviour (16). Decreasing sedentary behaviour could already produce health bene ts in people with stroke (6,10,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, long uninterrupted sedentary bouts are related to cardiovascular risks [13]. Interrupting SB after 20 minutes has been found to have a positive influence on glucose levels in overweight people [14], and interruption after 30 minutes decreased the systolic blood pressure of stroke survivors [15], thus providing cardiovascular health benefits.…”
Section: Introductionmentioning
confidence: 99%